Expression of deubiquitinases in human gingiva and cultured human gingival fibroblasts - Yong-Wei Fu; Hong-Zhi Xu (BMC, 2021)
Abstract Background Although deubiquitinating enzymes (DUBs) such as CYLD, A20 and OTULIN are expressed in multiple tissues and thought to be linked with inflammatory diseases, their expression in periodontal tissues remains to be determined. This research was designed to assess the expression of CYLD, A20 and OTULIN in human gingiva, and to evaluate the regulation of these DUBs in human gingival fibroblasts (HGFs) upon different stimuli. Methods Immunohistochemistry assay was conducted to determine the expression of CYLD, A20 and OTULIN in human gingiva. Immunofluorescence assay was employed to observe the protein expression of CYLD, A20 and OTULIN in HGFs. RT-PCR and western blots were carried out to assess gene and protein expression changes of these DUBs in HGFs upon LPS or TNF-α. Results CYLD, A20 and OTULIN were found to be expressed in human gingiva and HGFs. The expression of CYLD, A20 and OTULIN was lower in the inflamed gingival tissue samples compared with the healthy gingival tissue samples. Further, the expression of CYLD, A20 and OTULIN in HGFs exhibited distinct regulation by different stimuli. TNF-α treatment markedly increased NF-κB activation in HGFs Conclusions Our findings suggest that CYLD, A20 and OTULIN might play a role in the progression of periodontitis.